Knowledge and attitude to HIV pre exposure prophylaxis among women in five sub-Saharan African countries: a multilevel model analysis of population-based survey 2021–2022 - Bewuketu Terefe; Mahlet Moges Jembere; Dejen Kahsay Asgedom; Ayenew Molla Lakew (BMC Public Health, 2024)
Abstract Background HIV Pre-Exposure Prophylaxis (HIV PrEP) may help reduce the rate of HIV infection among women in sub-Saharan Africa (SSA). This study aimed to assess women’s knowledge and attitudes toward PrEP, a crucial component of HIV prevention, using nationwide data. It is the first study of its kind conducted in five SSA countries: Burkina Faso, Ghana, Côte d’Ivoire, Kenya, and Tanzania. The primary objective was to examine women’s knowledge and attitudes toward PrEP for the prevention of HIV infection, as well as to explore individual- and community-level factors associated with it. Methods The current study utilized the 2021/22 demographic and health survey datasets from five African nations, namely Burkina Faso, Côte d’Ivoire, Ghana, Kenya, and Tanzania. The analysis was performed using Stata 17. A weighted sample of 77,052 women of reproductive age participated in the survey. Univariate and multivariable multilevel logistic regressions were conducted to assess parameters related to knowledge and attitudes toward PrEP in these countries. In both the univariate regression and the final model, the significance of variables was determined using P values of ≤ 0.2 and < 0.05. Results Overall, only about 13.88 (95% CI: 13.64,14.12) of women had knowledge and attitudes toward HIV PrEP. The highest (34.29%) and lowest (5.61%) values were observed for Kenya and Tanzania respectively. Higher rates of knowledge, and attitude toward HIV PrEP among women were independently associated with age 25–34 years old (AOR = 1.52, 95% CI:1.41,1.64), and 35–49 years old (AOR = 1.56, 95% CI:1.43,1.69), primary education level (AOR = 1.79,95% CI:1.65,1.95), and secondary/higher education level (AOR = 2.92, 95% CI: 2.67,3.20), richer (AOR = 1.14, 95% CI:1.02,1.27), and richest (AOR = 1.21, 95% CI:1.06,1.37), employed women (AOR = 1.82, 95% CI:1.65,1.99), had media exposure (AOR = 1.49,95% CI:1.40,1.59),knowledge of modern contraception (AOR = 2.62, 95% CI: 1.94,3.43), had at least one ANC visit (AOR = 1.99, 95% CI:1.47,2.69), gave birth at health institutions (AOR = 1.17, 95% CI: 1.02,1.37), ever had given birth (AOR = 1.53, 95% CI: 1.41,1.66), female household heads (AOR = 1.24, 95% CI:1.17,1.31), rural women (AOR = 0.83, 95% CI: 0.76,0.89). Similarly, women from communities with high ANC coverage (AOR = 1.84, 95% CI: 1.61,2.11), high community mass media exposure (AOR = 1.62, 95% CI: 1.39,1.88), and high community wealth level (AOR = 1.48, 95% CI: 1.30,1.68), and women from the high illiteracy rate community (AOR = 0.71, 95% CI: 0.61,0.82) showed statistically significant associations with the outcome variable in the final model. Conclusions Less than one-seventh of women exhibited knowledge of and positive attitudes toward HIV PrEP. All stakeholders involved in HIV/AIDS prevention and control have recognized the significance of the factors mentioned above. Enhancing maternal health services, such as promoting institutional delivery, contraception, antenatal care (ANC), and women’s empowerment, alongside harnessing the power of media and embracing these transformative changes, will contribute to a greater understanding of and more favorable attitudes toward HIV PrEP within the population.